2009
DOI: 10.1007/s00420-009-0480-z
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of an interdisciplinary secondary prevention program for hairdressers

Abstract: The follow-up survey 9 months after the beginning of the program (response rate: IG: N = 163, 75.8%; CG: N = 80, 94.1%) showed that 71.8% (N = 117) of the intervention group could remain in work as opposed to 60.0% (N = 48) in the control group. In the intervention group 14.7% gave up work due to OSD versus 22.5% in the control group (no statistically significant effect). In the 5-year follow-up (response rate: IG: N = 172, 80%; CG: N = 55, 64.7%) 58.7% (N = 101) of the IG remained at work versus 29.1% (N = 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
56
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 26 publications
7
56
2
6
Order By: Relevance
“…The DGUV has published quality characteristics for skin prevention seminars . The positive and sustained effect of skin protection seminars has already been demonstrated by previous studies . The present study confirmed these findings, especially in terms of the patient remaining in his profession as a major goal of dermatological care of patients with occupational skin diseases.…”
Section: Discussionsupporting
confidence: 91%
“…The DGUV has published quality characteristics for skin prevention seminars . The positive and sustained effect of skin protection seminars has already been demonstrated by previous studies . The present study confirmed these findings, especially in terms of the patient remaining in his profession as a major goal of dermatological care of patients with occupational skin diseases.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, two third of our patients had a positive effect on clinical outcome that could be assigned to patient education alone or in combination with pharmacological treatment. These data are in agreement with previously published work indicating that interdisciplinary, secondary prevention programs, including integrated care for patients with hand eczema, result in a significant reduction of skin symptoms as well as an increased remaining at work [13,14]. In a randomized study, skin care education and individual counseling were shown to significantly improve symptoms and quality of life in health care workers with hand eczema [15].…”
Section: Discussionsupporting
confidence: 81%
“…The health education probably led to increased compliance and adherence with regard to the preventive strategies. This is supported by another study indicating that health education in patients with OSDs improves the long‐term prognosis regarding remaining in the workforce . In addition, other factors probably contributed to the beneficial effects of the TIP, especially the involvement of local dermatologists and employers.…”
Section: Discussionmentioning
confidence: 63%